Single Coronary Artery Anomaly: Case Report - Ajam, Firas; Udongwo, Ndausung; Upadhyaya, Vandan; Sathya, Bharath; Kiss, Daniel (Cardiology and Cardiovascular Medicine, 2021)
Single coronary anomaly is a rare congenital coronary artery disease where only one coronary artery arises from the aortic trunk, it could be an isolated finding or as part of other congenital cardiac diseases. We sought to present a patient with anginal symptoms was found to have single coronary artery.